The ‘unkabogable’ effect a reception analysis of Vice Ganda’s humor and its influence on Gen Z fans - Esparrago, Ed Gerwin G.; Sánchez, Louie Jon A. (Quezon City University of the Philippines Diliman, 2025)
Filipinos are known for their ability to find humor in almost everything, whether in the face of calamity, political turmoil, or diverging beliefs. Humor serves as a means of coping and a tool for social belonging, allowing Filipinos to shed light on issues concerning their society in a light manner. Vice Ganda is a prominent celebrity in the country who sheds light on these Filipino contemporary issues through her brand of humor; being vocal in her stance on these issues by using her humor, Vice Ganda’s case is unique as she has always had the power to use her brand of humor to make fun of these issues and always gather discourses around her jokes. Her humor engages in a wide array of themes, such as class inequality, gender politics, and Filipino societal values, thus offering audiences a space for an entertaining and critical reflection.

This study investigates how Vice Ganda’s humor is received by her Generation Z fans, called Little Ponies, focusing on how her humor contributes to the construction of their personal identities and social realities. The study will employ the six (6) dimensions of Schrøder’s Multidimensional Model of Mass Reception (2000) and Ancheta’s concept of Filipino humor (2011) to analyze how Gen Z fans of Vice Ganda receive and interpret her humor. Through qualitative methods, data were gathered from five (5) participants through an in-depth semi-structured interview to analyze the impact of Vice Ganda’s humor on her Gen Z fans concerning their personal identities and social realities.

Findings reveal that Vice Ganda’s humor resonates with her Gen Z fans because of its alignment with the characteristics of Filipino humor— subversive and reflective of shared cultural experiences. Vice Ganda’s comedy serves as an avenue for civic awareness and personal reflection, proving how her humor is perceived as entertaining and a reckoning force for identity negotiation, sociopolitical critique, and societal empowerment.
Thesis
Keywords: Television personalities -- Philippines; Humor -- Social aspects -- Philippines; Fans (Persons) -- Philippines